Developing Numerical Model of Debris Flow 2D as A Tool in Early Warning System - Jazaul Ikhsan, Sutikno Hardjosuwarno, Adam Pamuji Rahardjo (Disaster Prevention Research Institute, 2012)
The occurrences of debris flow in volcanic mountainous or non volcanic mountainous areas often cause disaster in surrounding rivers, so it had raised loss of lives and properties